2020
DOI: 10.1371/journal.pone.0227710
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analyses of quantitative disease resistance in diverse sets of soybean [Glycine max (L.) Merr.] plant introductions

Abstract: Phytophthora sojae is one of the costliest soybean pathogens in the US. Quantitative disease resistance (QDR) is a vital part of Phytophthora disease management. In this study, QDR was measured in 478 and 495 plant introductions (PIs) towards P. sojae isolates OH.121 and C2.S1, respectively, in genome-wide association (GWA) analyses to identify genetic markers linked to QDR loci (QDRL). Populations were generated by sampling PIs from the US, the Republic of Korea, and the full collection of PIs maintained by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 99 publications
(163 reference statements)
0
23
0
Order By: Relevance
“…Many known Rps genes are not effective towards all populations of P. sojae (Anderson et al., 2012; Costamilan et al., 2013; Dorrance et al., 2016; Kaitany et al., 2001; Ryley et al., 1998; Yan & Nelson, 2019; Yang et al., 2019), yet a wealth of data exits for the resistance reaction of PIs to various isolates with complex pathotypes (Matthiesen et al., 2016; Rolling et al., 2020; USDA GRIN database). Thus, the purpose of our study was to identify novel P. sojae resistance loci via GWA analyses from panels of soybean PIs with available P. sojae reaction data, especially with several isolates of complex pathotypes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many known Rps genes are not effective towards all populations of P. sojae (Anderson et al., 2012; Costamilan et al., 2013; Dorrance et al., 2016; Kaitany et al., 2001; Ryley et al., 1998; Yan & Nelson, 2019; Yang et al., 2019), yet a wealth of data exits for the resistance reaction of PIs to various isolates with complex pathotypes (Matthiesen et al., 2016; Rolling et al., 2020; USDA GRIN database). Thus, the purpose of our study was to identify novel P. sojae resistance loci via GWA analyses from panels of soybean PIs with available P. sojae reaction data, especially with several isolates of complex pathotypes.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 429 (Panel 3) and 460 (Panel 4) G. max accessions were phenotyped for resistance against the complex P. sojae isolates, OH.121 and C2.S1, respectively (Rolling et al., 2020). In Panel 3 and Panel 4, 46 and 22 G. max lines showed resistance to OH.121 (10.7%) and C2.S1 (4.8%), respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When available, MQTLs can be anchored to a reference genome, and relevant candidate genes could be proposed. A number of studies since 2009 are reported in crops for meta-QTL analysis of resistance against fungi and viruses, in order to propose valuable QTL to perform MAS, in particular in Theobroma cacao [ 78 ], barley [ 79 ], tetraploid cotton [ 80 , 81 ], pea [ 82 ], wheat [ 83 , 84 ], maize [ 85 ], peanut [ 86 ], grapevine [ 87 ], and soybean [ 88 ]. A study carried out in maize on the response to stem borers and storage pests feeding on leaves, stems, and kernels, from geographically diverse environments, pointed out the presence of a total of 104 resistance meta-QTLs from 382 individual QTLs, many of which were involved in several insect species, therefore generating a significant interest for multiple-insect resistance breeding [ 89 ].…”
Section: Toward the Identification Of Resistance Genes/locimentioning
confidence: 99%